1991
DOI: 10.1111/j.1432-1033.1991.tb15877.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and analysis of the human 46‐kDa mannose 6‐phosphate receptor gene

Abstract: From a genomic library in EMBL 3, two overlapping clones for the human 46-kDa mannose 6-phosphate receptor (MPR46) were isolated, which span the entire coding sequence. The human MPR46 gene is distributed over 12 kb and is divided into seven exons (110-1573 bp). All the intron/exon borders agree with the consensus sequences of splice junctions. Exon 1 codes for a 5' untranslated sequence. The ATG initiation codon begins with the second nucleotide in exon 2. A signal sequence of 26 amino acid residues is follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The Golgi lumens were swollen in HeLa cells and less pronouncedly in U2OS cells compared to those in the control cells, something also observed to a lesser extent in CQ-treated cells. Therefore, we also examined the distribution of M6PR (mannose-6-phosphate receptor, cation dependent), a protein cycling between the TGN and endosomes [39,40]. In agreement with the other observations, M6PR changed distribution in the presence of CQ, becoming more dispersed in punctate structures, whereas BafA 1 had no effect on the subcellular localization of this protein (Figure 3(D)).…”
Section: Cq Affects the Morphology Of Degradative Compartments Differsupporting
confidence: 86%
“…The Golgi lumens were swollen in HeLa cells and less pronouncedly in U2OS cells compared to those in the control cells, something also observed to a lesser extent in CQ-treated cells. Therefore, we also examined the distribution of M6PR (mannose-6-phosphate receptor, cation dependent), a protein cycling between the TGN and endosomes [39,40]. In agreement with the other observations, M6PR changed distribution in the presence of CQ, becoming more dispersed in punctate structures, whereas BafA 1 had no effect on the subcellular localization of this protein (Figure 3(D)).…”
Section: Cq Affects the Morphology Of Degradative Compartments Differsupporting
confidence: 86%
“…This contrast suggests that CDMPR plays important roles in lysosomal enzyme trafficking in non-hepatocyte cells of the liver. Promoter analyses of human and mouse CDMPR genes have shown that they contain CpG islands and lack a TATA box, suggesting that CDMPR is expressed constitutively as a housekeeping gene (Klier et al 1991;Ludwig et al 1992), whereas the expression of CIMPR is regulated by several transcription factors (Liu et al 1995). Such gene characteristics of CDMPR may correspond with its rather broad expression in rat liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the extracytoplasmic domain of CD-M6PR is homologous to the approximately 145 amino acid long repeating domains present in the CI-M6PR with sequence identity *Address correspondence to this author at the Inserm unité 826, Bâtiment recherche, CRLC Val d'Aurelle, 34298 Montpellier, France; E-mail: m.garcia@valdorel.fnclcc.fr ranging from 14 to 28%. These studies allowed to conclude that these two receptors located on different chromosomes (12p13 and 6q26, respectively) have diverged from a common ancestral gene [13,14].…”
Section: Structure Of Mannose 6-phosphate Receptors and Ligand Multipmentioning
confidence: 97%